Aproksymacja prawdopodobieństwa ruiny dla gaussowskiego procesu ryzyka - Dębicki, Krzysztof (Approximations of the Ruin Probability for a Gaussian Risk Process, 2006)
The family of Gaussian stochastic processes is widely used as a reach source of models in applied probability, including actuarial and financial mathematics. The paper reviews some recent results dealing with the approximation of the ruin probability under the condition that the risk process is modeled by a Gaussian stochastic process with stationary increments. General results are illustrated by two special classes of examples: fractional Brownian motions and integrated Gaussian processes.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1108, s. 231-243